Factors That Influence Maternal Child Health Nurses’ Identification of Risk of Family Violence to First Nations Women in Australia - Catherine Louise Austin (International Journal of Environmental Research and Public Health, 2025)
Aim: To understand the factors that influence family violence towards First Nations women, to inform practises and policies to support these women and improve their engagement in maternal child health services. Design: A qualitative study, using narrative inquiry integrated with the Indigenous philosophy ‘Dadirri’, and thematic analysis of the data. Materials and Methods: Survey of 10 Maternal Child Health nurses in 2019, and interviews of 35 Aboriginal mothers in 2021. Results: The nurses identified drugs, alcohol, socio-economic issues, the history of effects of colonisation on First Nations peoples, and stress as perceived factors influencing family violence, and acceptance, fear, cultural beliefs, and mistrust, for women’s low reporting of violence. Factors that influenced nurses’ ability to identify family violence were mistrust and understanding of Aboriginal culture. Low self-esteem, lack of belonging, and not being heard were identified by the mothers as factors that influence family violence. Fear of child protective services, shame, mistrust, and poor rapport with the nurses contributed to their low reporting of violence. The most significant factor for the mothers to disclose violence is fear of losing her child, mistrust, and the questioning process. Conclusions: Nurses’ understanding of Indigenous culture is critical to develop trust and improve the engagement of First Nations women. A significant difference in the synthesis of data between the nurses and their First Nations consumers was conspicuous. Research regarding the benefit of models and interventions that recognise the social determinants of health and well-being on health outcomes as well as the value of culturally strong health services aimed to encourage an earlier identification of risk, ideally from the antenatal period to the child’s fifth birthday, is imperative. The implications of this research are of international importance for First Nations families and challenge current nursing practises to address the human rights challenge of ...